The Ownership of the Firm, Corporate Finance, and Derivatives Some Critical Thinking - Chang, Kuo-Ping.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book clarifies several ambiguous arguments and claims in finance and the theory of the firm. It also serves as a bridge between derivatives, corporate finance and the theory of the firm. In addition to mathematical derivations and theories, the book also uses anecdotes and numerical examples to explain some unconventional concepts. The main arguments of the book are: (1) the ownership of the firm is not a valid concept, and firms$1 (Bobjectives are determined by entrepreneurs who can innovate to earn excess profits; (2) the Modigliani-Miller capital structure irrelevancy proposition is a restatement of the Coase theorem, and changes in the firm$1 (Bs debt-equity ratio will not affect equity-holders$1 (Bwealth (welfare), and equity-holders$1 (Bpreferences toward risk (or variance) are irrelevant; (3) all firms' resources are options, and every asset is both a European call and a put option for any other asset; and (4) that a first or residual claim between debt and equity is non-existent while the first claim among fixed-income assets can actually affect the market values of these assets.s
Preface -- Chapter 1: The Ownership of the Firm -- 1.1: A Story of Robin Hood -- 1.2: Power, Entrepreneur, and Objectives of the Firm -- 1.3: Choice, Risk Attitude, and Types of Contract -- References -- Chapter 2: Maximizing Profits and Maximizing Resource Providers$1 (BWealth -- 2.1: The Coase Theorem and the Modigliani-Miller Propositions -- 2.2: A Simple Example of the Modigliani-Miller Second Proposition -- References -- Chapter 3: A Reconsideration of the Modigliani-Miller Propositions -- 3.1: A Tale of Two Cows-The Modigliani-Miller First Proposition -- 3.2: Some Fallacious Arguments for the Modigliani-Miller Second Proposition -- References -- Chapter 4: Derivatives and the Theory of the Firm -- 4.1: Model-Free Option Prices -- 4.2: The Firm$1 (Bs Resources and Derivatives -- 4.2.1: Each Resource Is Both a European Call Option and a European Put Option -- 4.2.2: Each Resource Is a Stock Plus a Forward Contract -- References -- Chapter 5: Arbitrage and Valuation of Different Contracts -- 5.1: The Arbitrage Theorem -- 5.2: Properties of the Binomial Option Pricing Model -- 5.3: Valuing Different Contracts -- Appendix A: Incomplete Market -- Appendix B: Incomplete Market and Replication of Securities -- Appendix C: More Uncertain Project and the Firm$1 (Bs Value -- References -- Chapter 6: Misinterpretations of Residual Claim in Finance and Corporate Law -- 6.1: De Jure versus De Facto -- 6.2: Agency Costs and Residual Claim -- 6.3: Moral Hazard and Residual Claim -- References -- Index.s
Keywords: Economics; Microeconomics; Finance; Economics/Management Science; Finance/Investment/Banking.; Microeconomics; Financial Economics